DETERMINATION THE OCCURANCE OF MERCURY IN SOIL IN THE MINING AREA OF ROMANG ISLAND - Hendarto, Rudhy (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2017)
The occurance of mercury in the environment whether on land, water and air can occur because of human activities or naturally existed. In gold mining activities, the source of mercury occurrence can be from the mining activity or being naturally exist in the land and water. Romang Island is one of the islands in the Maluku Islands. In the Romang Island, currently being done the process of exploring the potential of mining materials. Metallic minerals to be explore on Romang Island included Gold (Au) and associated metal minerals such as Silver (Ag), Copper (Cu), Zinc (Zn), Lead (Pb) and Manganese mineral (Mn ). This study aims to determine the occurrence of mercury in the soil in Romang Island. This research is very important to understand whether the mercury in Romang Island is natural existed or available due to the mining activities. In order to determine the mercury in the soil, laboratory test was conducted. Soil samples were taken using non-probability sampling method: accidental sampling and purposive sampling. Selection of this sampling method is done with consideration of limited road accessibility on Romang island and security. From the results of laboratory tests, we found that mercury in Romang Island is naturally existed. The value range from 0.223 to 1.627 ppm. The natural existence of mercury in the Romang Island is quite possible given the geological conditions on this area.